PROFIL USAHA BUBUR JAGUNG MUTIARA DI MALALAYANG SATU TIMUR MANADO - Evangelista Ch. Ray-Ray; Hanny Anapu; Theodora M. Katiandagho; Vicky R.B. Moniaga (Universitas Sam Ratulangi, 2013)
AbstractThe objective of this research is to determine the profile of the business grits pearls. This study uses primary data obtained through interview techniques directly to business owners using questionnaires. The method of data analysis used in this study is a descriptive analysis of data. Data collected are presented in tabular form, and then the analysis costs, revenue, profits, and break-even point analysis is used.The results of this research indicated this business received a profit of Rp. 2.097.043 for a month of production. The results of analysis of the break-even point in this business, when production volume amounted to 376 grits pearls to glass for 5 times the production process. Business owners foresight in seeing the market opportunity and the selection of the strategic place of business, resulted in business is quite promising and may increase the family income.Based on this research it can be concluded that the business grits pearls is household-scale business. There was no bookkeeping in this business and, business owners also concurrently into labor. Therefore, it is necessary to the holding of bookkeeping about business grits pearls by business owners and increase the workforce to expand the business grits pearl. The results of the analysis ratio of R/C of 1,2 indicates that the business is feasible to be developed. In addition, this business has aesthetic value in which business owners are not limited to for-profit but it refers to the service to consumers.